Effects of Ga, Ge and As Modification on Structural, Electrochemical and Electronic Properties of Li2MnSiO4. Issue 15 (20th November 2019) - Yan, Xiaotong; Hou, Yuhua; Huang, Youlin; Zheng, Shouhong; Shi, Zhiqiang; Tao, Xiaoma
Abstract : Effects of Ga, Ge and As doping on structural, electrochemical and electronic properties of Li-ion battery cathode material Li2 MnSiO4 are systematically studied by the first-principles calculations based on density functional theory within the generalized gradient approximation with Hubbard corrections (GGA+ U ). The calculated results show that the doping of Ga, Ge and As can reduce the deintercalation voltages of extraction for the first Li + in per formula unit. For Ge doping, the appearance of Jahn-Teller distortion of Mn 3+ ion can be delayed, and the cell volume would shrink with the removal of Li +, thus, the good cyclic stability can be realized. Ga doping exhibits better cycle performance, however, the deintercalation voltage is relatively high when Li + ions are completely removed in per formula unit. The doping of As makes the deintercalation voltages reduce, nevertheless, the expansion of the cell volume and the distortion for the bond of As-O suggest that it is not beneficial in improving the cycling performance of Li2 MnSiO4 as cathode material for Li-ion battery. In addition, based on the electronic structure and magnetic properties, the influence mechanism of doping on the cyclic stability and electrochemical properties are investigated in details for Li2 MnSiO4 cathode material.